Tinjauan Perkawinan di Bawah Umur Menurut Perspektif Hukum Nasional dan Hukum Islam: Perkawinan di bawah umur, Perkawinan di bawah umur menurut hukum Islam, Perkawinan di bawah umur menurut hukum Islam, Dampak perkawinan di bawah umur - Qorin Annida Salma; Eko Wahyu Ramadani (CV Rewang Rencang, 2025)
Underage marriage is a marriage between a man and a woman or one of them either by force or certain conditions who are not yet 19 years old. There are differences regarding the minimum age at which a person can marry according to Islamic law and Indonesian positive law. Where in Islamic law it is not certain how old a person can marry, while in the national setting the minimum limit for marriage is 19 years for both men and women. The existence of these differences gives rise to legal pluralism. The data collection technique used is Library Research, namely by collecting supporting data from books, journals, articles, documents, and online media. The analysis method used is the descriptive analysis method. Because Islamic law and national law are complementary and incompatible. This is because Islam does not encourage underage marriage because it causes many consequences and consequences. The writing of this study uses a qualitative approach method with the type of library research.